60 COMPARISON OF METABOLIC EQUIVALENT WITH THE 6-MINUTE WALK TEST AS A MEASURE OF EXERCISE CAPACITY AND OUTCOME PREDICTOR IN PULMONARY ARTERIAL HYPERTENSION: RESULTS FROM THE INTRAVENOUS TREPROSTINIL STUDY. (1st March 2006) - Gomberg-Maitland, M.; Huo, D.; Tapson, V. F.; McLaughlin, V. V.; Benza, R. L.; Barst, R. J.
Abstract : Purpose: The 6-Minute Walk Test (6MW) is the recommended test to assess exercise capacity in pulmonary arterial hypertension (PAH). Metabolic equivalent (MET) is the amount of oxygen used by a seated person and is a predictor of survival in the general population. We sought to determine if the two tests had good repeated reliability and determine their ability to predict functional class and/or hemodynamic parameters. Methods: Forty-seven PAH patients enrolled in a prospective open-label 12-week trial of intravenous treprostinil. At baseline, week 6, and week 12 both 6MW followed by Naughton-Balke treadmill tests were preformed (> 30 minutes apart) in addition to NYHA Functional Class (FC). Hemodynamic measures were recorded at baseline and week 12. Treadmill time in seconds was converted to MET based on the protocol. Baseline data are expressed as means ± SD. Pearson correlation coefficient ( r ) was calculated to express interrelationships between measures of exercise capacity. Intraclass correlation coefficient (ICC) was used to indicate the repeated reliability of exercise measures over time. Linear regression assessed the relationship between CO, mPA, and exercise capacity and logistic regression assessed the relationship between FC and exercise capacity. GEE population average modeling compared change in FC and/or hemodynamic measures with exercise outcomes. Two-sided p values < .05 were statistically significant. Results: Mean values at baseline: 404 ± 98 m, 495 ± 263 sec, 5.6 ± 2 MET and at week 12: 425 ± 88m, 563 ± 239 sec, 6.1 ± 1.9 MET. Values for both tests were normally distributed. Treadmill time and METS were highly correlative, r = .99 (p < .001). ICCs for 6MW, treadmill time, and MET were 0.77, 0.82, and 0.80, respectively. FC correlated with 6MW and MET at baseline and at week 12 (all p < .01). CO correlated with exercise at baseline (6MW, p = .01; MET, p < .001) but not at week 12; mPA did not correlate with either test. Conclusions: MET is a reliable exercise measure in PAH patients and correlates with 6MW. Exercise capacity measures highly correlated with FC but not consistently correlated with resting hemodynamics. One-year data will allow more comparative data.